Analysis Analysis of the KPPU’s Role in Providing Recommendations and Considerations on Government Policy - Laily Ika Nuraini; Dita Perwitasari; Syaffiqa Noer Husnina Putrie (Indonesian Journal of Administrative Law and Local Government, 2026)
Government sectoral policies can create barriers to a healthy competitive business environment, particularly when certain businesses are granted preferential treatment. Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition mandates the Business Competition Supervisory Commission (KPPU) to provide recommendations and considerations regarding government policies that have the potential to cause unfair business competition. However, the law does not provide clarity regarding the legal status of the KPPU’s recommendations, their binding nature, or the legal consequences if such recommendations are not implemented. This study aims to analyze the KPPU’s role in providing recommendations and considerations regarding government policies that have the potential to create an imbalance in business competition, as well as to examine the legal consequences of disregarding such recommendations and considerations. Using a statutory and conceptual approach, this study analyzes Law No. 5 of 1999, KPPU Regulation No. 4 of 2023, and a concrete case involving the Ministry of Energy and Mineral Resources’ Circular Letter No. T-19/MG.05/WM.M/2025 regarding import restrictions in the downstream oil and gas sector. The research findings indicate that the KPPU functions as an independent institution with the authority to issue advisory and preventive recommendations that lack coercive power. The KPPU’s recommendations and considerations are not legally binding and do not result in direct sanctions if not implemented. However, disregarding the KPPU’s recommendations and considerations has the potential to result in indirect legal consequences, such as a weakening of policy legitimacy, potential violations of the general principles of good governance, and the possibility of administrative lawsuits if the policy is proven to be detrimental to businesses and consumers. Keywords: KPPU, government policy, unfair business competition, recommendations and considerations